1997
DOI: 10.1007/s002449900176
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Binary Chemical Mixtures: Effects on Reproduction of Zebrafish ( Brachydanio rerio )

Abstract: A complete life-cycle test with zebrafish was carried outwith different concentrations of the binary mixture 3,4-dichloroaniline andlindane under flow-through conditions. Length and weight of fish of theF1-generation were reduced, even in the lowest test concentrationof 2 microg/L 3,4-dichloroaniline and 40 microg/L lindane. The same effects werefound in the early life stage test for the F2-generation. In themixture of 100 microg/L 3,4-dichloroaniline and 40 microg/L lindane, fish whichwere exposed for their w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…This reduction in sperm released could therefore be due to the influences of the xenobiotic on the endocrine system as stated Mattison and Thomson, 17) Donaldson and Scherer 18) More recently, Schettler 11) reported that in general wildlife studies demonstrated a relationship between exposures to endocrine disrupting substances and abnormal thyroid function, sex alterations, poor hatching success, decreased fertility and growth, and altered behavior. On the other hand, the reduction in egg production and decreased fertility reported by Ensenbach and Nagel 22) during the investigation of the effect of Dichloroaniline and Lindane on the reproduction of zebrafish could have been due to the negative effects of the chemicals on the sperm released by the male fish as found in the present experiment. How far these modifications in hormone concentrations lead to the decrease of sperm released by the male zebrafish is not known.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…This reduction in sperm released could therefore be due to the influences of the xenobiotic on the endocrine system as stated Mattison and Thomson, 17) Donaldson and Scherer 18) More recently, Schettler 11) reported that in general wildlife studies demonstrated a relationship between exposures to endocrine disrupting substances and abnormal thyroid function, sex alterations, poor hatching success, decreased fertility and growth, and altered behavior. On the other hand, the reduction in egg production and decreased fertility reported by Ensenbach and Nagel 22) during the investigation of the effect of Dichloroaniline and Lindane on the reproduction of zebrafish could have been due to the negative effects of the chemicals on the sperm released by the male fish as found in the present experiment. How far these modifications in hormone concentrations lead to the decrease of sperm released by the male zebrafish is not known.…”
Section: Discussionsupporting
confidence: 48%
“…Reduced fertilization rates in exposed group as compared to controls may have different causes: direct effect of the substance on spermatogenesis, effect on the released sperm only or on the eggs by change of the egg membrane to the effect that penetration of intact spermatozoa is hindered or prevented. Finally more recently, Ensenbach and Nagel 22) reported that one of the most important effects of xenobiotics on fish is the impairment of reproduction. According to all these reports, why not seeking to establish whether DDT for e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of 3,4-dichloroaniline and lindane had an additive effect and influenced growth somewhat in early life stages of small fish (69). If the fish were exposed for the whole life span, they stopped reproducing (70). There was no single clear-cut mechanism to explain the toxicity of 4-nitro-and 2,4-dinitroaniline to various environmental eukaryotes and prokaryotes (71).…”
Section: Studies On Environmental Impactmentioning
confidence: 91%
“…The early life stages of fish provide an array of developmental parameters, which could serve as biomarkers of toxicant effects (Nagel 2002;Hallare et al 2004;Braunbeck et al 2005). The impact of toxicants on embryo growth and ontogeny could be extrapolated to assess effects at population levels (Ensenbach and Nagel 1997). Apart from its sensitivity, this test offers practical advantages over fish acute toxicity tests.…”
Section: Significance Of Using Fish Embryosmentioning
confidence: 99%